Strategi Pemasaran Madrasah dalam Meningkatkan Daya Saing di Madrasah Ibtidaiyah at-Taqwa Bondowoso - Holilah, Mega Nur; Royani, Ahmad; Tsauri, Sofyan (MANAGIERE: Journal of Islamic Educational Management, 2022)
the purpose of this article is to describe strategies in the form of place, price, promotion and product marketing strategies in increasing the competitiveness of institutions at MI At-Taqwa Bondowoso. Research using qualitative research methods using descriptive analysis. The results of the study show that: 1) The marketing strategy for madrasas in increasing the competitiveness of institutions is by strategically located madrasah locations or places, besides that the classrooms are quite spacious with nuances of beauty in each class, namely the presence of an ornament from student creativity that can build imagination good and eager to learn. 2) The marketing strategy for madrasa promotion in increasing the competitiveness of institutions is to use print media strategies, online media, Word of Moth, and direct promotions every day by providing new innovations such as friendly Friday and alms Friday activities. 3) The marketing strategy for madrasah prices in increasing the competitiveness of institutions is to offer prices in accordance with the quality of education services provided and to carry out market preferences using psychographic segmentation and demographic segmentation, and to establish price marketing segmentation with measurable analysis with consumer data, community behavior, affordability aspects, and sustainability of benefits. 4) The marketing strategy for madrasa products in increasing the competitiveness of institutions is to bring up many new innovations by creating pesantren-style education, namely by having superior programs such as the tahfidz class program, the program to memorize asmaul husna, the program to memorize lay aqidatul, the dhuha prayer program, the congregational dhuhur prayer program, and the sholawat program, while also improving the quality of teachers and adequate facilities and infrastructure.